From Global Consciousness to Social Action: An Examination of Adult Education Theory - Lilian H. Hill (Adult Education Research Conference, 1998)
This paper links 1) social action theories in adult education, and 2) literature about the transition to a global consciousness, a world view emerging in the latter part of this century. Global consciousness does not emanate from a single body of literature, but exists within many disciplines.